PENGGUNAAN APE DENGAN PENDEKATAN MONTESSORI UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA 3-4 TAHUN DI PPT DAHLIA I SURABAYA - Theresia, Angelia; Sari, Anisa Yunita (MOTORIC, 2025)
ABSCTRACT Angelia Theresia, 05119007. Use of educational game tools with a Montessori approach to Improve Fine Motor Skills in Children Aged 3-4 Years at PPT Dahlia I Surabaya This study is to find out how efforts are being made to improve children's fine motor skills through APE with the Montessori approach. Based on the reality at PPT DAHLIA I Surabaya's children still encounter obstacles in their fine motor skills. Children are more happy with games in general than games that require calm and motoric skills. Out of 15 children, only 6 children who can beading well. The research was carried out using a classroom action research model. The research subjects were the 3-4 year old age group with the analysis techniques used were average values, percentages and graphs. In order to obtain valid results, it is carried out using research techniques through two cycles of cycle steps, and each cycle consists of four stages, namely Planning, Implementation, Observation and Reflection. Based on the results of the study it turned out that activities to improve children's fine motor skills through APE activities with the Montessori approach at PPT DAHLIA I Surabaya seemed to increase in the very well developed category. This can be seen from the final results of the implementation of cycle I with a percentage of 40%. Then in cycle II, the percentage of successful children was 82%. With these improvements, children have the opportunity to develop their fine motor skills through APE activities with a Montessori approach. Thus, APE with the Montessori approach does help in the development of children's fine motor skills. Keywords: Fine motor skills, use of APE with theMontessori Approach, Classroom Action Research